COMPUTATION OF BEARING CAPACITY FACTOR Nq –TERZAGHI AND PRANDTL MECHANISM - D.M. Dewaikar; B.G. Mohapatro; V.A. Sawant; H.S. Chore (Universitas Gadjah Mada, 2008)
The unique values of the bearing capacity factors, Nq are obtained in respect of failure mechanisms suggested by Terzaghi and Prandtl using limit equilibrium approach. In this paper an attempt has been made to present the analysis integrating the Kotter’s equation with Terzaghi’s and Prandtl’s mechanisms using limit equilibrium conditions. The analysis presented here with some modifications in the exiting analyses computes the bearing capacity factor – Nq , the expressions of which are similar to the one given by Terzaghi [10] and Reissner [7] who had extended the pioneering work initiated by Prandtl [6]. The analysis reported here successfully demonstrates the applicability of Kotter’s equation to the solution of limit equilibrium problems involving plane or curved failure surfaces.